Handicaps associated with incontinence: implications for management. Issue 3 (September 1990) - McGrother, C W; Jagger, C; Clarke, M; Castleden, C M
Abstract : STUDY OBJECTIVE--The aim was to explore the relationship between dementia, impairment of mobility, and incontinence and the implications for management. DESIGN--The study was a survey of a sample population drawn from a general practice register. SETTING--A large general practice serving the entire population of Melton Mowbray, Leicestershire, UK. PARTICIPANTS--Of 1329 persons aged 75 or over, 1203 (90%) took part in the survey. Of non-responders, refusers accounted for 5%, deaths 4%, and failure to trace 1%. MEASUREMENTS AND MAIN RESULTS--12% of the population complained of incontinence. No more than 24% of these cases were demented. Dementia and isolated locomotor problems were significantly associated with presence of incontinence, but 31% of cases were completely free of either problem. A minimum estimate of 56% of cases of incontinence were considered to be due to local physical disorders of the bladder. CONCLUSIONS--A search for local disorders causing incontinence is important, and more attention should be paid to the management of locomotor problems and possibly depression in the relief of incontinence.